2013
DOI: 10.1038/jcbfm.2013.171
|View full text |Cite
|
Sign up to set email alerts
|

[11C]5-HTP and microPET are Not Suitable for Pharmacodynamic Studies in the Rodent Brain

Abstract: The PET tracer [(11)C]5-hydroxytryptophan ([(11)C]5-HTP), which is converted to [(11)C]5-hydroxytryptamine ([(11)C]5-HT) by aromatic amino acid decarboxylase (AADC), is thought to measure 5-HT synthesis rates. But can we measure these synthesis rates by kinetic modeling of [(11)C]5-HTP in rat? Male rats were scanned with [(11)C]5-HTP (60 minutes) after different treatments. Scans included arterial blood sampling and metabolite analysis. 5-HT synthesis rates were calculated by a two-tissue compartment model (2T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Preclinical experiments with [ 11 C] 5 -HTP have been performed to study AADC activity/serotonin synthesis in the rhesus monkey, , rat, and mice . A study of [ β - 11 C]­HTP metabolism in monkeys found that the parent fraction in plasma gradually decreased to ∼50% at 60 min, with [ 11 C]­hydroxyindoleacetic acid ([ 11 C]­HIAA) being the major metabolite (39%) .…”
Section: Amino Acidsmentioning
confidence: 99%
“…Preclinical experiments with [ 11 C] 5 -HTP have been performed to study AADC activity/serotonin synthesis in the rhesus monkey, , rat, and mice . A study of [ β - 11 C]­HTP metabolism in monkeys found that the parent fraction in plasma gradually decreased to ∼50% at 60 min, with [ 11 C]­hydroxyindoleacetic acid ([ 11 C]­HIAA) being the major metabolite (39%) .…”
Section: Amino Acidsmentioning
confidence: 99%
“…47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,and 65) In the management of NETs 68 Ga-DOTA-conjugated peptide, PET/CT is used to localise primary tumours and detect sites of metastatic disease (staging); follow-up patients with known disease to detect residual, recurrent or progressive disease (restaging); determine somatostatin status; monitor response to therapy; and select patients with metastatic disease for peptide receptor radionuclide therapy (Skoura et al 2016;Sundin 2018;Singh et al 2018;Waseem et al 2019). Nitro-group are postulated to undergo reduction in hypoxic condition (pO2 ≤ 2-3 mmHg), forming highly reactive oxygen radicals that subsequently bind covalently to macromolecules inside the cells (Visser et al 2014;Orlefors et al 2005 (Fig. 67) PET-CT with 18 F-FMISO is a non-invasive method for detecting and characterising hypoxia in several tumours.…”
Section: Scan Acquisitionmentioning
confidence: 99%
“…Nitro-group are postulated to undergo reduction in hypoxic condition (pO2 ≤ 2–3 mmHg), forming highly reactive oxygen radicals that subsequently bind covalently to macromolecules inside the cells (Visser et al 2014 ; Orlefors et al 2005 ).…”
Section: Radiopharmaceuticalsmentioning
confidence: 99%
“…In the brain, serotonin (5-hydroxytryptamine, 5-HT), the core molecule of the system, acts as a neurotransmitter and is associated with the feeling of wellness and happiness [3]. Altered regulation of serotonin concentration in the brain has been recorded not only in a vast range of behavioral functions, such as wake/sleep states, appetite, and sexual behavior, but also in the causation of multiple severe psychotic disorders, such as depression, bipolar disorder, and schizophrenia [4,5]. Although the roles of serotonin in the brain have been intensively investigated, the serotonergic function in peripheral organs, where serotonin acts as a hormonal molecule, is mostly uninvestigated, even though 95% of the serotonin in the whole body is produced by the gastrointestinal tract [6].…”
Section: Introductionmentioning
confidence: 99%